2021
DOI: 10.17645/mac.v9i1.3205
|View full text |Cite
|
Sign up to set email alerts
|

Assassins, Gods, and Androids: How Narratives and Game Mechanics Shape Eudaimonic Game Experiences

Abstract: Emerging research has suggested that digital games can generate entertainment experiences beyond hedonic enjoyment towards eudaimonic experiences: Being emotionally moved, stimulated to reflect on one’s self or a sense of elevation. Studies in this area have mainly focused on individual game characteristics that elicit singular and static eudaimonic game moments. However, such a focus neglects the interplay of multiple game aspects as well as the dynamic nature of eudaimonic experiences. The current study take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
11
0
3
Order By: Relevance
“…One reason for this could be found in Vandewalle et al (2022), in which Assassin's Creed players felt that some of the game worlds (especially in the open-world format games based in antiquity) were generally repetitive, sometimes recycling assets that were obvious to players (repeating scenery or structures, etc.). Another study that focused on Assassin's Creed Odyssey (in comparison to other games, see Daneels, Malliet et al, 2021) found that the game's "level-grinding" mechanics (in which players are required to engage in smaller tasks to progress a game) are likely barriers to emotional engagement necessary for appreciation to form.…”
Section: Appreciation and Historical Gamingmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for this could be found in Vandewalle et al (2022), in which Assassin's Creed players felt that some of the game worlds (especially in the open-world format games based in antiquity) were generally repetitive, sometimes recycling assets that were obvious to players (repeating scenery or structures, etc.). Another study that focused on Assassin's Creed Odyssey (in comparison to other games, see Daneels, Malliet et al, 2021) found that the game's "level-grinding" mechanics (in which players are required to engage in smaller tasks to progress a game) are likely barriers to emotional engagement necessary for appreciation to form.…”
Section: Appreciation and Historical Gamingmentioning
confidence: 99%
“…This finding was surprising, given that both were associated with enjoyment in Vandewalle et al (2022). One argument for this finding is that both freedom of choice and simulational realism focus on what the player can do within a historical video game-allowing the player to reenact and influence history while they play (see Chapman, 2016; and thus, feel a deeper emotional connection with those experiences (Daneels, Malliet et al, 2021) Connecting these findings to sense of place, it is possible that players enjoy historical games when those games are able to provide impressive and detailed places to connect with (especially relevant for recreating ancient history in video games, to help "close the gaps" for players entering the atmosphere of antiquity), and they appreciate historical games when they are able to freely move through and directly experience and test those places (especially relevant for recreating modern history in video games, to help reimagine otherwise recognizable spaces for players).…”
Section: Ancillary Findings Associated With Perceived Realismmentioning
confidence: 99%
“…This condition showed that the GoW series was a versatile medium for various game mechanic experimentation (design of the quick time events, side-scroller play), control schemes (changes from the controller of the console into a portable version), and mode of interfaces (i.e., stereoscopic 3D of GoW: Origins collection). Furthermore, different marketing schemes (collections of high-definition remastered GoW releases) and business model development (downloadable contents) were also explored, which provided eudaimonic experiences and narrative engagement of the play [32]. Such situations were due to the well-blend mechanics' support and key narrative themes provided by the series.…”
Section: B Analyzing God Of War Seriesmentioning
confidence: 99%
“…Este videojuego se enmarca en un futuro poshumano. Daneels et al (2021) encuentran que la narrativa de este juego produce experiencias eudaimónicas en los jugadores. Igualmente, en una investigación cualitativa orientada a la interacción humano-robot, Craig et al (2020) examinaron las estrategias que utilizó un grupo de videojugadores de Detroit: Become Human en las elecciones de su avatar y su apego emocional a los androides del juego.…”
Section: Palavras-chave (Fonte: Tesauro Da Unesco)unclassified